Dampak Program Pekarangan Pangan Lestari (P2L) Terhadap Tingkat Kecukupan Gizi (TKG) - Reny Sukmawani; Endang Tri Astutiningsih; Livia Ramadanti (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2022)
Over the past two years, the COVID-19 pandemic has had various impacts on various sectors. The implementation of the sustainable food yard program (P2L) launched by the Ministry of Agriculture is one of the efforts to overcome its impact. This study aims to determine the impact of the implementation of the P2L program on the level of nutritional adequacy (TKG) which was carried out during the covid-19 pandemic. This study aims to determine the impact of the implementation of P2L program on the level of nutritional adequacy (TKG). This research is a case study conducted in the Women Farmers Group (KWT) Walidah, Cisaat District, Sukabumi Regency. The results showed that after the implementation of the P2L program during the pandemic, it had a positive impact on households in terms of nutritional adequacy. Based on that, the P2L program should be carried out in a sustainable manner.